2017
DOI: 10.1016/j.bbadis.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Novel patient missense mutations in the HSD17B10 gene affect dehydrogenase and mitochondrial tRNA modification functions of the encoded protein

Abstract: MRPP2 (also known as HSD10/SDR5C1) is a multifunctional protein that harbours both catalytic and non-catalytic functions. The protein belongs to the short-chain dehydrogenase/reductases (SDR) family and is involved in the catabolism of isoleucine in vivo and steroid metabolism in vitro. MRPP2 also moonlights in a complex with the MRPP1 (also known as TRMT10C) protein for N1-methylation of purines at position 9 of mitochondrial tRNA, and in a complex with MRPP1 and MRPP3 (also known as PRORP) proteins for 5'-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…In patients in whom the diagnosis of MATD was based on metabolite data only (without rather labile 2methylacetoacetic acid), but not confirmed on enzyme and/or mutation level, it needs to be considered that patients were possibly not affected by MATD but by HSD10 mitochondrial disease (HSD10MD; OMIM 300438). HSD10 mitochondrial disease is caused by a hemizygous or heterozygous mutation in the HSD17B10 gene [23,24]. The suspicion that patients actually had HSD10 mitochondrial disease prompted us to exclude two brothers from this study, who have been reported as beta-ketothiolase deficient by Jänisch et al 1993 andHesse et al 2004 [25,26], but in whom we consider published clinical and enzyme data rather nonsuggestive for MATD.…”
Section: Discussionmentioning
confidence: 99%
“…In patients in whom the diagnosis of MATD was based on metabolite data only (without rather labile 2methylacetoacetic acid), but not confirmed on enzyme and/or mutation level, it needs to be considered that patients were possibly not affected by MATD but by HSD10 mitochondrial disease (HSD10MD; OMIM 300438). HSD10 mitochondrial disease is caused by a hemizygous or heterozygous mutation in the HSD17B10 gene [23,24]. The suspicion that patients actually had HSD10 mitochondrial disease prompted us to exclude two brothers from this study, who have been reported as beta-ketothiolase deficient by Jänisch et al 1993 andHesse et al 2004 [25,26], but in whom we consider published clinical and enzyme data rather nonsuggestive for MATD.…”
Section: Discussionmentioning
confidence: 99%
“…MRPP2 (also known as HSD10/SDR5C1) belongs to the short-chain dehydrogenase/reductases (SDR) family and is involved in the catabolism of isoleucine and steroid metabolism [ 14 ]. MRPP2 also interacts in a complex with MRPP1 (TRMT10C) and MRPP3 (also known as PRORP), proteins involved in 5′-end processing of mitochondrial precursor tRNA [ 5 ].…”
Section: Maturation Of the Primary Transcript: Pre-rna Processingmentioning
confidence: 99%
“…Two additional patients were reported with variable severity of developmental delay, epilepsy, and cardiac involvement. As a hallmark of the disease, urinary organic acid analysis showed elevated levels of 2-methyl-3-hydroxybutyric acid and tiglylglycine, and abnormalities were also detected in the acyl-carnitine spectrum in some cases [ 14 ].…”
Section: Maturation Of the Primary Transcript: Pre-rna Processingmentioning
confidence: 99%
“…This last Trm10 homolog is a component of the mitochondrial RNaseP complex (Holzmann et al 2008), in which TrmT10C forms a subcomplex with the dehydrogenase HSD10. Association of TrmT10C with HSD10 is required for tRNA MTase activity (Vilardo and Rossmanith 2015;Oerum et al 2017b).…”
Section: Introductionmentioning
confidence: 99%